Production method of corrosion-resistant hot-dip galvanized aluminum magnesium photovoltaic structure steel with tensile strength of 440 MPa

By using carbon and manganese alloying design and adding titanium in photovoltaic structural steels, combined with zinc, aluminum, and magnesium plating, the problems of high corrosion resistance and low-cost steels in the existing technology are solved, and high strength and corrosion resistance are achieved Steel for photovoltaic structures.

CN119464901APending Publication Date: 2025-02-18BAOTOU IRON & STEEL (GROUP) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410747953.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to develop high-strength steel suitable for photovoltaic structures while ensuring high corrosion resistance and low cost.

Method used

By adopting carbon and manganese alloy solid solution reinforcement design and adding a small amount of titanium to improve the angle crack defect of the casting billet, reducing the manganese content to reduce costs, and at the same time, zinc-aluminum-magnesium (Zn-6%Al-3%Mg) is used on the surface of the strip steel. Coating to improve corrosion resistance.

Benefits of technology

The corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with tensile strength ≥440MPa, yield strength ≥335MPa and elongation ≥18% was achieved. The corrosion resistance performance was improved by 5 to 10 times, reducing the product usage cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464901A_ABST
    Figure CN119464901A_ABST
Patent Text Reader

Abstract

The invention discloses a production method of corrosion-resistant hot-dip galvanized aluminum magnesium photovoltaic structural steel with tensile strength of 440 MPa, which is characterized in that the steel comprises the following chemical components in percentage by weight: 0.17-0.20% of C, less than or equal to 0.05% of Si, 0.60-0.80% of Mn, less than or equal to 0.020% of P, less than or equal to 0.010% of S, 0.015-0.045% of Alt, 0.030-0.050% of Ti, 0.0008-0.0020% of Ca and the balance of Fe and inevitable impurities, and the invention also discloses a specific preparation process of the steel. According to the invention, the alloy cost of the product is greatly reduced on the basis of reaching the required strength of the product through the recarburization and manganese reduction component design, the mechanical properties meet the following conditions: the yield strength is greater than or equal to 335MPa, the tensile strength is greater than or equal to 440MPa, the elongation (L0 = 80mm, b0 = 20mm) is greater than or equal to 18%, and the product strength design meets the formability of simple stamping deformation of a bending machine for steel for a photovoltaic structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal material processing and manufacturing technology, and in particular to a production method of corrosion-resistant grade hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440 MPa. Background Art

[0002] In recent years, the international community has proposed energy conservation and emission reduction to reduce carbon emissions. At present, solar photovoltaic power generation can effectively reduce carbon emissions and achieve green power generation. Therefore, in recent years, the country has vigorously promoted photovoltaic power generation construction projects. The demand for steel equipment required for photovoltaic power generation construction is also increasing year by year. The development of high corrosion-resistant hot-dip galvanized aluminum-magnesium products can meet the high corrosion resistance required by photovoltaic assembly parts, and the market demand and profit indicators of the products are obviously superior to ordinary galvanized products. While enriching the product structure of the enterprise, the profit is also improved. With the increase of green electricity indicators for manufacturing products at home and abroad, the future development prospects of hot-dip galvanized aluminum-magnesium products required for photovoltaic power generation will be broader and have broad market promotion prospects.

[0003] The search patent number CN 115181888 A is "Yield Strength 450MPa Grade Low Carbon Low Alloy Hot-dip Aluminum-Zinc or Zinc-Aluminum-Magnesium Duplex Steel and Its Manufacturing Method". It was found that the patent composition design adopts the solid solution strengthening mechanism design of carbon, silicon, manganese, chromium or niobium and titanium elements to meet the product design requirements, the manganese content is controlled at a high level of 1.0-1.6%, and the continuous annealing cooling adopts a low temperature design. The strip steel structure is a complex phase structure of at least three structures in ferrite, martensite, bainite, micron-sized precipitates, and deformed banded grains. The product metallographic structure is complex and the product structure is complex and unstable; although the patent involves the hot-dip galvanizing aluminum-magnesium rights method, the description does not mention the proportion of each element in the zinc-aluminum-magnesium coating, and the patent ownership content is unclear. Compared with the search patent, the composition design of the present invention adopts carbon and manganese alloying solid solution strengthening, and adds a trace amount of titanium to improve the process design of the corner crack defect of the ingot. Although the carbon content design is slightly higher than that of the search patent, the alloy manufacturing cost is lower, which greatly reduces the product alloy cost on the basis of meeting the design requirements of product strength. The carbon content of the present invention is 0.17-0.20%, the manganese content ranges from 0.60-0.80%, the strip structure is ferrite and pearlite, and the product chemical composition and strength design are different from the search patent 1; the proportions of each element of the coating type zinc, aluminum and magnesium are 6% aluminum, 3% magnesium, and 91% zinc respectively. The present invention clarifies the composition of the coating.

[0004] The searched patent number CN 115161542 A is "550MPa grade hot-dip aluminum-zinc or zinc-aluminum-magnesium complex phase steel and its manufacturing method". After checking, the patent composition design adopts carbon, silicon, manganese, chromium or niobium and titanium elements solid solution strengthening mechanism design to meet the product design requirements, and the yield strength is 550MPa, which is different from the strength level of the present invention; the strip steel structure is a complex phase structure of at least three structures in ferrite, martensite, bainite, micron-sized precipitates, and deformed banded grains. The product metallographic structure is complex and unstable; although the patent involves the hot-dip zinc-aluminum-magnesium rights method, the description does not mention the proportion of each element in the zinc-aluminum-magnesium coating, and the patent ownership is unclear. Compared with the searched patent, the composition design of the present invention adopts carbon and manganese alloying solid solution strengthening design, and adds a small amount of titanium to improve the corner crack defects of the casting. Compared with the searched patent, the alloy cost of the present invention is lower, and the designed yield strength ≥335MPa and tensile strength ≥440MPa can be achieved by increasing the carbon content and reducing the manganese content. Therefore, the chemical composition and design strength of this product are different from those of the searched patent 2, and the strip structure is ferrite and pearlite; the proportions of each element of the coating types zinc, aluminum and magnesium are respectively 6% aluminum, 3% magnesium and 91% zinc, and the present invention clarifies the composition of the coating; compared with the corrosion resistance of the strip surface plated with pure zinc, the strip surface of the present invention is plated with zinc, aluminum and magnesium corrosion-resistant coating, and the corrosion resistance of the product can be improved by 5 to 10 times, which greatly extends the service life of the steel and reduces the product use cost.

[0005] The search patent number CN 112680684 A is "A hot-dip galvanized aluminum-magnesium alloy coating and its preparation method". After checking, the content of the patent is the preparation method of zinc-aluminum-magnesium coating, not the hot-dip galvanized aluminum-magnesium process of steel strip, and the technical field involved is completely different. The chemical composition percentage of the prepared hot-dip galvanized aluminum-magnesium alloy coating includes the coating type used in the present invention. Compared with the search patent, the present invention involves a preparation method of corrosion-resistant hot-dip galvanized aluminum-magnesium steel strip. By selecting the coating type, the proportion of each element of zinc, aluminum and magnesium is respectively: 6% aluminum, 3% magnesium, and 91% zinc coating design, the corrosion resistance of steel is greatly improved, and the corrosion resistance of strip steel can be increased by 5 to 10 times, which greatly extends the service life of steel and reduces the cost of product use. Summary of the invention

[0006] The purpose of the present invention is to provide a production method of corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440MPa. The solid solution strengthening of the product is achieved by adopting carbon and manganese chemical composition design, and a small amount of titanium is added to improve the corner crack defects of the ingot. Compared with the low-carbon design concept adopted in the search patent, the present invention greatly reduces the product alloy cost on the basis of achieving the required strength of the product by increasing carbon and reducing manganese composition design. The mechanical properties meet the following requirements: yield strength ≥335MPa, tensile strength ≥440MPa, elongation (L0=80mm, b0=20mm) ≥18%. The product strength design meets the performance of simple stamping deformation of photovoltaic structure steel bending machine. The slabs that meet the design requirements of chemical composition are processed by hot rolling, pickling, pickling and annealing. The strip steel passes through a hot melting pot with a certain temperature to store liquid zinc-aluminum-magnesium (Zn-6%Al-3%Mg), so that the surface of the strip steel is evenly coated with zinc-aluminum-magnesium solution. According to the user's requirements for the coating weight, the air knife process is used to control the coating thickness of different thicknesses, and produce 250MPa-grade corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel strips. Its product strength, forming shape, and corrosion resistance can meet the user's design requirements.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] The invention discloses a production method of corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440 MPa. The chemical composition of the steel is C: 0.17-0.20%, Si: ≤0.05%, Mn: 0.60-0.80%, P≤0.020%, S≤0.010%, Alt: 0.015-0.045%, Ti: 0.030-0.050%, Ca: 0.0008-0.0020%, and the balance is Fe and inevitable impurities. The hot rolling process produces a casting billet according to the required chemical composition, and the billet is cooled or hot-charged into a hot rolling heating furnace. The heating temperature is different according to the rolling thickness, and the heating temperature ranges from 1200 to 1270°C, the furnace time is 150-230 minutes, and the soaking time is 20-55 minutes. in, furnace temperature 1180 ~ 1250 ℃, finishing rolling process final rolling temperature 870 ~ 920 ℃, coiling temperature 560 ~ 640 ℃; pickling process according to the finished product thickness requirements, the reduction rate setting range 52% ~ 76%; galvanizing process continuous annealing furnace process strip heating / soaking control temperature adopts 700 ~ 740 ℃, slow cooling temperature range 620 ~ 660 ℃, strip fast cooling / zinc pot temperature range 450 ~ 490 ℃, zinc aluminum magnesium molten liquid temperature control range 430 ± 20 ℃; strip skin straightening process according to the thickness requirements of the elongation control range of 0.7 ~ 1.3%, the elongation range of the straightening machine ≤ 0.4%; after the above process requirements, the corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel strip with a tensile strength of 440MPa is obtained.

[0009] Furthermore, the method specifically comprises the following preparation steps:

[0010] (1) KR desulfurization → converter smelting → LF refining → slab continuous casting;

[0011] (2) Slab heating → high-pressure water descaling → fixed width press → E1R1 roughing mill rolling → E2R2 roughing mill rolling → insulation cover → flying shear head and tail → high-pressure water descaling → F1~F7 finishing mill rolling → encrypted laminar cooling → coiling → pallet transportation system → weighing → storage;

[0012] (3) Pickling and uncoiling → welding → straightening → pickling → rinsing → drying → trimming → rolling → coiling → weighing → marking → bundling → storage;

[0013] (4) Hot-dip galvanizing uncoiling → welding → entrance looper → cleaning → annealing furnace → zinc pot → cooling after plating → water quenching → intermediate looper → skin pass machine → stretch straightening machine → roller coating machine → dryer → air cooling device → exit looper → trimming → surface inspection → (oiling) → sampling and inspection → coiling → bundling and weighing → packaging → storage;

[0014] in:

[0015] At the end of the KR process, the sulfur content in the molten iron should be ≤0.010%, and the slag removal ratio on the surface of the molten iron tank should be ≥90%. The tapping temperature of the converter should be controlled at ≥1620℃. During the tapping process, ferromanganese and ferroaluminum are added to the ladle to deoxidize and alloy the molten steel. At the beginning and end of the converter tapping, a slide plate is used to block the slag to prevent the converter slag from entering the ladle.

[0016] After the ladle is in place during the LF refining process, slag is made and desulfurized. The refining slag should achieve a white slag effect, and the (FeO+MnO) content in the slag should be less than 1.5%. Aluminum iron, manganese iron, titanium iron, etc. are added for final deoxidation and alloying, and adjusted to the target composition range. LF is off-site to ensure that the S content in the molten steel is ≤0.010%; calcium treatment is carried out after the LF treatment is completed. During the calcium treatment process, a high calcium line of 200m is fed to control the reasonable argon flow rate to prevent the molten steel from being exposed; after calcium treatment, the soft blowing time is guaranteed to be ≥8 minutes to improve the cleanliness control of the molten steel;

[0017] During the casting process, the ladle is protected by argon gas. During the large ladle pouring process, the slag detection equipment is turned on. When the large ladle pouring is finished, the slag from the large ladle is prevented from flowing into the tundish. During the casting process, the casting machine adopts constant pulling speed control, and the pulling speed setting range is 1.1m / min~1.8m / min according to different casting sections. The tundish pouring superheat is controlled at 15℃~30℃. Ingot inspection: the center segregation of the continuous casting ingot shall not be greater than Class B 1.5, and the center looseness shall not be greater than 1.0.

[0018] The hot rolling process adopts hot or cold charging into the furnace for heating; the appropriate heating system is selected according to the thickness specification requirements, the heating temperature range is 1200-1270℃, the furnace time is 150-230min, the soaking temperature range is 1180-1250℃, the soaking temperature is 20-55min, and the furnace discharge temperature is 1180-1250℃;

[0019] The rolling process includes rough rolling and finishing rolling. The rough rolling adopts a 2-stand rolling mill, and the finishing rolling adopts a 7-stand continuous variable crown rolling mill. The final rolling temperature of the finishing rolling is 870-920°C. The cooling adopts a laminar continuous cooling device, the cooling code is set to 11 mode, the upper cooling nozzle is one-on-one, and the lower cooling nozzle is two-on-one. The coiling temperature is controlled in the range of 560-640°C according to the thickness.

[0020] In the pickling and pickling process, the reduction rate is controlled within the range of 52-76% according to the order thickness requirements. In order to ensure good adhesion of the coating to the strip surface in the next process, the surface roughness of the roller in the pickling process is 2.0-3.0μm. At the end of rolling, the surface roughness of the strip must be greater than 1.0μm, so as to ensure good adhesion between the strip and the galvanized steel, and avoid defects such as missing plating, coating shedding, and cracks on the strip surface.

[0021] Continuous hot-dip galvanizing process, annealing process adopts vertical continuous annealing furnace, the atmosphere in the furnace should be cooled by reducing protective atmosphere, the heating process is based on the strip thickness heating / averaging temperature range 700 ~ 740 ℃, slow cooling temperature 620 ~ 660 ℃, fast cooling temperature 450 ~ 490 ℃, strip entering the zinc pot temperature 450 ~ 490 ℃, zinc aluminum magnesium melt temperature range 425 ~ 435 ℃; coating thickness is based on order requirements, select the appropriate air knife pressure; furnace zone steel strip speed according to different thickness 70 ~ 130m / min, flat mill elongation 0.7 ~ 1.3%, straightening machine elongation ≤ 0.4%.

[0022] Further, it specifically includes:

[0023] The molten iron is pretreated for desulfurization, and the S content of the molten iron leaving the desulfurization station is 0.001%. The heating amount of the desulfurizer in the treatment process is 0.3 tons, the stirring time is 15 minutes, the number of slag removal is greater than 1 time, the slag removal rate is greater than 90%, and the molten iron leaving the station temperature T is 1312°C; the top and bottom combined blowing converter is used for smelting to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process. The weight of scrap steel added to the converter is 45.1 tons, the weight of molten iron added to the converter is 261 tons, the converter tapping temperature is 1629°C, the tapping carbon content is 0.07%, and the tapping process is 1629°C. Ferromanganese and ferroaluminum are added to the ladle for deoxidation and alloying. Slide plates are used to block slag before and after steelmaking to prevent slag. 1800 kg of high-carbon ferromanganese and 1250 kg of ferroaluminum are added during the deoxidation and alloying process. Then, the molten steel after converter smelting is subjected to LF refining outside the furnace. The refining temperature is 1534℃. LF refining slag deoxidation and desulfurization are carried out, and the composition temperature is adjusted. Alloying treatment is carried out in the early stage of LF treatment, and 630 kg of ferromanganese, 300 kg of ferroaluminum, and 200 kg of ferrotitanium are added. 260 meters of calcium wire is fed into the calcium treatment line for alloying. After the slag is formed into white slag, calcium treatment is carried out, the soft blowing time is 10 minutes, and the soft blowing process prevents the leakage of molten steel. The LF refining leaving station temperature is 1575℃; the casting machine pouring overheat is 20℃, the pulling speed is 1.30m / min, and the slag detection is turned on after the ladle pouring, and the gate slide operation is automatically closed to avoid slag in the middle ladle; after the quality inspection of the slab, it is loaded into the heating furnace. The thickness of the hot rolled slab is 3.8mm, the heating temperature is 1221℃, the heating time is 203min, the soaking time is 30min, and the furnace temperature is 12 05℃, the heated slab is dephosphorized by high-pressure water; the width is set by a fixed-width press, 2-stand rough rolling is adopted, the rough rolling adopts the 3+5 mode, and the 7-stand CVC finishing rolling is adopted, and the finishing rolling temperature is 892℃; the laminar cooling adopts the continuous cooling method 11, and the coiling temperature is 582℃; the reduction rate of the pickling process is set to 60%; the rolling thickness of the galvanizing process is 1.5mm, the annealing furnace heating / soaking temperature is 721℃, the slow cooling temperature is 635℃, the fast cooling temperature is 461℃, the zinc pot temperature is 430℃, and the coating thickness is set to 275g / m 2 The speed of the steel strip in the furnace zone is set at 100m / min, the elongation of the leveler is 1.21%, and the elongation of the straightening machine is 0.35%.

[0024] Further, the method specifically includes: pre-treatment of molten iron with desulfurization, the S content of molten iron leaving the desulfurization station is 0.001%, the heating amount of desulfurizer in the treatment process is 0.3 tons, the stirring time is 15 minutes, the number of slag removal is more than 1 time, the slag removal rate is more than 90%, and the molten iron leaving the station temperature T is 1334℃; top and bottom combined blowing converter smelting is used to decarbonize and dephosphorize the molten iron to obtain molten steel, argon is blown throughout the converter smelting process, the weight of scrap steel added to the converter is 51.2 tons, the weight of molten iron added to the converter is 257 tons, the converter tapping temperature is 1638℃, and the tapping carbon content is 0. 05%. During the steel-making process, ferromanganese and ferroaluminum are added to the ladle for deoxidation and alloying. Slide plates are used to block slag before and after steel-making to prevent slag. 1720 kg of high-carbon ferromanganese and 1340 kg of ferroaluminum are added during the deoxidation and alloying process. Then the molten steel after converter smelting is subjected to LF refining outside the furnace. The refining temperature is 1542℃. LF refining slags, deoxidizes, desulfurizes, and adjusts the component temperature. In the early stage of LF treatment, alloying treatment is carried out, 562 kg of ferromanganese, 420 kg of ferroaluminum, and 220 kg of ferrotitanium are added. 280 kg of calcium is fed into the calcium line for calcium treatment. m, after alloying, the slag forms white slag and then undergoes calcium treatment. The soft blowing time is 11 min. During the soft blowing process, no steel liquid leaks out. The temperature of LF refining station is 1581°C. The casting machine pouring overheat is 24°C, the pulling speed is 1.20 m / min, and the slag detection is turned on after the ladle pouring, and the gate slide operation is automatically closed to avoid slag in the middle ladle. After the slab is quality checked, it is loaded into the heating furnace. The thickness of the hot rolled slab is 4.8 mm, the heating temperature is 1212°C, the heating time is 172 min, the soaking time is 35 min, and the furnace temperature is 1581°C. The temperature is 1195℃, and the heated slab is dephosphorized by high-pressure water; the width is set by a fixed-width press, 2-stand rough rolling is adopted, the rough rolling adopts the 3+5 mode, and the 7-stand CVC finishing rolling is adopted, and the finishing rolling temperature is 880℃; the laminar cooling adopts the continuous cooling method 11, and the coiling temperature is 570℃; the reduction rate of the pickling process is set to 58%; the rolling thickness of the galvanizing process is 2.0mm, the annealing furnace heating / soaking temperature is 708℃, the slow cooling temperature is 629℃, the fast cooling temperature is 465℃, the zinc pot temperature is 430℃, and the coating thickness is set to 275g / m 2 The speed of the steel strip in the furnace zone is set at 90m / min, the elongation of the leveler is 1.10%, and the elongation of the straightening machine is 0.30%.

[0025] Compared with the prior art, the beneficial technical effects of the present invention are:

[0026] Through reasonable chemical composition design and the above production method, a corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440MPa can be obtained. Compared with the same-level products on the market, in order to ensure good product formability, the chemical composition generally adopts a low-carbon design, while the present invention adopts a carbon-increasing and manganese-reducing composition design to reduce the cost of manganese alloys. While ensuring product performance and forming, the product alloy cost is greatly reduced, and the product welding performance is improved. The surface of the strip steel of the present invention adopts a zinc-aluminum-magnesium Zn-6%Al-3%Mg coating design, which greatly improves the corrosion resistance of the steel. Compared with ordinary galvanized products, the corrosion resistance is increased by 5 to 10 times, the service life of the steel is extended, and the cost of steel use is reduced. According to the chemical composition design and rolling process provided by the patent, corrosion-resistant zinc-aluminum-magnesium strip steel that fully meets the design requirements for strength and formability can be produced. The product yield strength is ≥335MPa, the tensile strength is ≥440MPa, the elongation is ≥18%, and the coating adhesion and cold bending performance meet the design standard requirements. The implementation and promotion of the present invention can greatly improve product profitability while enriching the product structure of the enterprise, improve product quality and efficiency, and enhance the market competitiveness of the enterprise. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described below in conjunction with the accompanying drawings.

[0028] Figure 1 This is a surface diagram of a steel strip according to Embodiment 1 of the present invention;

[0029] Figure 2 This is a surface diagram of the strip steel according to the second embodiment of the present invention. DETAILED DESCRIPTION

[0030] The present invention is described in more detail below with examples. These examples are merely descriptions of the best mode for carrying out the present invention and are not intended to limit the scope of the present invention in any way.

[0031] Embodiment 1

[0032] The molten iron is pretreated for desulfurization, and the S content of the molten iron leaving the desulfurization station KR is 0.001%. The heating amount of the desulfurizer in the treatment process is 0.3 tons, the stirring time is 15 minutes, the slag removal times are greater than 1 time, the slag removal rate is greater than 90%, and the molten iron leaving the station temperature T is 1312°C; the molten iron is decarburized and dephosphorized to obtain molten steel by top and bottom combined blowing converter smelting, argon is blown throughout the converter smelting process, the weight of scrap steel added to the converter is 45.1 tons, the weight of molten iron added to the converter is 261 tons, the converter tapping temperature is 1629°C, the carbon content of the tapping is 0.07%, ferromanganese and ferroaluminum are added to the ladle during the tapping process for deoxidation and alloying, and a slide plate is used to block the slag before and after tapping to prevent slag, and 1800 kg of high carbon ferromanganese and 1250 kg of ferroaluminum are added during the deoxidation and alloying process. Then the molten steel after converter smelting is subjected to LF refining outside the furnace, and the refining temperature is 1534℃. The LF refining slag is deoxidized and desulfurized, and the composition temperature is adjusted. The alloying treatment is carried out in the early stage of LF treatment, and 630 kg of ferromanganese, 300 kg of ferroaluminum, and 200 kg of ferrotitanium are added. 260 meters of calcium wire is fed for calcium treatment. After the alloying is completed, the slag forms white slag and then calcium treatment is carried out. The soft blowing time is 10 minutes. The soft blowing process prevents the steel liquid from leaking. The LF refining leaving station temperature is 1575℃. The casting machine is supplied with the chemical composition shown in Table 1. The casting machine pouring superheat is 20℃, the pulling speed is 1.30m / min, and the slag detection is turned on after the ladle pouring, and the gate slide operation is automatically closed to avoid slag in the middle ladle. After quality inspection of the slab, it is loaded into the heating furnace. The hot rolled slab is 3.8mm thick, the heating temperature is 1221℃, the heating time is 203min, the soaking time is 30min, the furnace temperature is 1205℃, and the heated slab is subjected to high-pressure water dephosphorization. The width is determined by a fixed-width press, and 2-stand rough rolling (rough rolling adopts 3+5 mode), 7-stand CVC finishing rolling, and the finishing temperature is 892℃. Laminar cooling adopts continuous cooling method 11, and the coiling temperature is 582℃. The reduction rate of the acid rolling process is set to 60%. The rolling thickness of the galvanizing process is 1.5mm, the annealing furnace heating / saturation temperature is 721℃, the slow cooling temperature is 635℃, the rapid cooling temperature is 461℃, the zinc pot temperature is 430℃, and the coating thickness is set to 275g / m 2 The speed of the steel strip in the furnace is set at 100 m / min, the elongation of the leveler is 1.21%, and the elongation of the straightening machine is 0.35%. The corresponding mechanical properties of the finished product are shown in Table 2.

[0033] Embodiment 2

[0034] The molten iron is pretreated for desulfurization, and the S content of the molten iron leaving the desulfurization station KR is 0.001%. The heating amount of the desulfurizer in the treatment process is 0.3 tons, the stirring time is 15 minutes, the slag removal times are greater than 1 time, the slag removal rate is greater than 90%, and the molten iron leaving the station temperature T is 1334°C; the molten iron is decarburized and dephosphorized to obtain molten steel by top and bottom combined blowing converter smelting, argon is blown throughout the converter smelting process, the weight of scrap steel added to the converter is 51.2 tons, the weight of molten iron added to the converter is 257 tons, the converter tapping temperature is 1638°C, the carbon content of the tapping is 0.05%, and ferromanganese and ferroaluminum are added to the ladle during the tapping process for deoxidation and alloying. A slide plate is used to block the slag before and after tapping to prevent slag. 1720 kg of high carbon ferromanganese and 1340 kg of ferroaluminum are added during the deoxidation and alloying process. Then the molten steel after converter smelting is subjected to LF refining outside the furnace, and the refining temperature is 1542℃. The LF refining slag is deoxidized and desulfurized, and the composition temperature is adjusted. The alloying treatment is carried out in the early stage of LF treatment, and 562 kg of ferromanganese, 420 kg of ferroaluminum, and 220 kg of ferrotitanium are added. 280 meters of calcium wire is fed for calcium treatment. After the alloying is completed, the slag forms white slag and then calcium treatment is carried out. The soft blowing time is 11 minutes. The soft blowing process prevents the steel liquid from leaking. The LF refining leaving station temperature is 1581℃. The casting machine is supplied with the chemical composition shown in Table 1. The casting machine pouring superheat is 24℃, the pulling speed is 1.20m / min, and the slag detection is turned on after the ladle pouring, and the gate slide operation is automatically closed to avoid slag in the middle ladle. After quality inspection of the slab, it is loaded into the heating furnace. The thickness of the hot-rolled slab is 4.8mm, the heating temperature is 1212℃, the heating time is 172min, the soaking time is 35min, the furnace temperature is 1195℃, and the heated slab is subjected to high-pressure water dephosphorization. The width is determined by a fixed-width press, and 2-stand rough rolling (rough rolling adopts 3+5 mode), 7-stand CVC finishing rolling, and the finishing temperature is 880℃. Laminar cooling adopts continuous cooling method 11, and the coiling temperature is 570℃. The reduction rate of the acid rolling process is set to 58%. The rolling thickness of the galvanizing process is 2.0mm, the annealing furnace heating / saturation temperature is 708℃, the slow cooling temperature is 629℃, the rapid cooling temperature is 465℃, the zinc pot temperature is 430℃, and the coating thickness is set to 275g / m 2 The speed of the steel strip in the furnace is set at 90 m / min, the elongation of the leveler is 1.10%, and the elongation of the straightening machine is 0.30%. The corresponding mechanical properties of the finished product are shown in Table 2.

[0035] It can be seen from the actual values ​​of chemical composition in Table 1 and the test values ​​of mechanical properties of finished coils in Table 2 that through the implementation of cases 1, 2, and 3, the chemical composition and mechanical properties of the steel coils produced meet the user requirements, and the product formability, strength, and corrosion resistance all meet the use requirements.

[0036] Table 1 LF refining casting machine chemical composition (%)

[0037] C Si Mn P S Alt Ca Ti Example 1 0.17 0.020 0.67 0.016 0.006 0.032 0.00010 0.035 Example 2 0.17 0.020 0.67 0.016 0.006 0.032 0.00011 0.036

[0038] Table 2 Mechanical properties of finished products corresponding to the implementation cases

[0039] Thickness / mm Yield strength / MPa Tensile strength / MPa Elongation / % Example 1 1.50 386~401 513~521 29.5~30.0 Example 2 2.00 380~409 509~528 24.5~27.0

[0040] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for producing corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440 MPa, characterized in that: Its chemical composition is C: 0.17-0.20%, Si: ≤0.05%, Mn: 0.60-0.80%, P≤0.020%, S≤0.010%, Alt: 0.015-0.045%, Ti: 0.030-0.050%, Ca: 0.0008-0.0020%, and the balance is Fe and inevitable impurities; the hot rolling process produces the ingot according to the required chemical composition, and after cooling or hot charging, it enters the hot rolling heating furnace. The heating temperature is different according to the rolling thickness, the heating temperature range is 1200-1270°C, the furnace time is 150-230min, the soaking time is 20-55min, and the furnace temperature is 1180-1250°C. The final rolling temperature of the finishing rolling process is 870-920℃, and the coiling temperature is 560-640℃; the pickling process has a reduction rate setting range of 52%-76% according to the thickness requirements of the finished product; the continuous annealing furnace process of the galvanizing process adopts a strip heating / heating control temperature of 700-740℃, a slow cooling temperature range of 620-660℃, a strip fast cooling / zinc pot temperature range of 450-490℃, and a zinc-aluminum-magnesium melt temperature control range of 430±20℃; the strip skin-smoothing and straightening process has an elongation control range of 0.7-1.3% according to the thickness requirements, and the elongation range of the straightening machine is ≤0.4%; after the above-mentioned process requirements are controlled, a corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel strip with a tensile strength of 440MPa is obtained.

2. The production method of corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440 MPa according to claim 1 is characterized in that: The specific preparation process includes the following steps: (1) KR desulfurization → converter smelting → LF refining → slab continuous casting; (2) Slab heating → high-pressure water descaling → fixed width press → E1R1 roughing mill rolling → E2R2 roughing mill rolling → insulation cover → flying shear head and tail → high-pressure water descaling → F1~F7 finishing mill rolling → encrypted laminar cooling → coiling → pallet transportation system → weighing → storage; (3) Pickling and uncoiling → welding → straightening → pickling → rinsing → drying → trimming → rolling → coiling → weighing → marking → bundling → storage; (4) Hot-dip galvanizing uncoiling → welding → entrance looper → cleaning → annealing furnace → zinc pot → cooling after plating → water quenching → intermediate looper → skin pass machine → stretch straightening machine → roller coating machine → dryer → air cooling device → exit looper → trimming → surface inspection → (oiling) → sampling and inspection → coiling → bundling and weighing → packaging → storage; in: At the end of the KR process, the sulfur content in the molten iron should be ≤0.010%, and the slag removal ratio on the surface of the molten iron tank should be ≥90%. The tapping temperature of the converter should be controlled at ≥1620℃. During the tapping process, ferromanganese and ferroaluminum are added to the ladle to deoxidize and alloy the molten steel. At the beginning and end of the converter tapping, a slide plate is used to block the slag to prevent the converter slag from entering the ladle. After the ladle is in place during the LF refining process, slag is made and desulfurized. The refining slag should achieve a white slag effect, and the (FeO+MnO) content in the slag should be less than 1.5%. Aluminum iron, manganese iron, titanium iron, etc. are added for final deoxidation and alloying, and adjusted to the target composition range. LF is off-site to ensure that the S content in the molten steel is ≤0.010%; calcium treatment is carried out after the LF treatment is completed. During the calcium treatment process, a high calcium line of 200m is fed to control the reasonable argon flow rate to prevent the molten steel from being exposed; after calcium treatment, the soft blowing time is guaranteed to be ≥8 minutes to improve the cleanliness control of the molten steel; During the casting process, the ladle is protected by argon gas. During the large ladle pouring process, the slag detection equipment is turned on. When the large ladle pouring is finished, the slag from the large ladle is prevented from flowing into the tundish. During the casting process, the casting machine adopts constant pulling speed control, and the pulling speed setting range is 1.1m / min~1.8m / min according to different casting sections. The tundish pouring superheat is controlled at 15℃~30℃. Ingot inspection: the center segregation of the continuous casting ingot shall not be greater than Class B 1.5, and the center looseness shall not be greater than 1.

0. The hot rolling process adopts hot or cold charging into the furnace for heating; the appropriate heating system is selected according to the thickness specification requirements, the heating temperature range is 1200-1270℃, the furnace time is 150-230min, the soaking temperature range is 1180-1250℃, the soaking temperature is 20-55min, and the furnace discharge temperature is 1180-1250℃; The rolling process includes rough rolling and finishing rolling. The rough rolling adopts a 2-stand rolling mill, and the finishing rolling adopts a 7-stand continuous variable crown rolling mill. The final rolling temperature of the finishing rolling is 870-920°C. The cooling adopts a laminar continuous cooling device, the cooling code is set to 11 mode, the upper cooling nozzle is one-on-one, and the lower cooling nozzle is two-on-one. The coiling temperature is controlled in the range of 560-640°C according to the thickness. In the pickling and pickling process, the reduction rate is controlled within the range of 52-76% according to the order thickness requirements. In order to ensure good adhesion of the coating to the strip surface in the next process, the surface roughness of the roller in the pickling process is 2.0-3.0μm. At the end of rolling, the surface roughness of the strip must be greater than 1.0μm, so as to ensure good adhesion between the strip and the galvanized steel, and avoid defects such as missing plating, coating shedding, and cracks on the strip surface. Continuous hot-dip galvanizing process, annealing process adopts vertical continuous annealing furnace, the atmosphere in the furnace should be cooled by reducing protective atmosphere, the heating process is based on the strip thickness heating / averaging temperature range 700 ~ 740 ℃, slow cooling temperature 620 ~ 660 ℃, fast cooling temperature 450 ~ 490 ℃, strip entering the zinc pot temperature 450 ~ 490 ℃, zinc aluminum magnesium melt temperature range 425 ~ 435 ℃; coating thickness is based on order requirements, select the appropriate air knife pressure; furnace zone steel strip speed according to different thickness 70 ~ 130m / min, flat mill elongation 0.7 ~ 1.3%, straightening machine elongation ≤ 0.4%.

3. The production method of corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440 MPa according to claim 1 is characterized in that: Specifically include: The molten iron is pretreated for desulfurization, and the S content of the molten iron leaving the desulfurization station is 0.001%. The heating amount of the desulfurizer in the treatment process is 0.3 tons, the stirring time is 15 minutes, the number of slag removal is greater than 1 time, the slag removal rate is greater than 90%, and the molten iron leaving the station temperature T is 1312°C; the top and bottom combined blowing converter is used for smelting to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process. The weight of scrap steel added to the converter is 45.1 tons, the weight of molten iron added to the converter is 261 tons, the converter tapping temperature is 1629°C, the tapping carbon content is 0.07%, and ferromanganese and ferroaluminum are added to the ladle during the tapping process. Deoxidation and alloying are carried out. Slide plates are used to block slag before and after steelmaking to prevent slag. 1800 kg of high-carbon ferromanganese and 1250 kg of ferroaluminum are added during the deoxidation and alloying process. Then the molten steel after converter smelting is subjected to LF refining outside the furnace. The refining temperature is 1534℃. LF refining slag deoxidation and desulfurization are carried out, and the component temperature is adjusted. Alloying treatment is carried out in the early stage of LF treatment. 630 kg of ferromanganese, 300 kg of ferroaluminum, and 200 kg of ferrotitanium are added. 260 meters of calcium wire are fed for calcium treatment. After the alloying is completed, the slag forms white slag and calcium treatment is carried out. The soft blowing time is 10m in, the soft blowing process prevents the leakage of molten steel, the LF refining leaving the station temperature is 1575℃; the casting machine pouring overheat is 20℃, the pulling speed is 1.30m / min, the slag detection is turned on after the ladle pouring, and the gate slide operation is automatically closed to avoid slag in the middle ladle; after the slab quality inspection, it is loaded into the heating furnace, the hot rolled slab thickness is 3.8mm, the heating temperature is 1221℃, the heating time is 203min, the soaking time is 30min, the furnace temperature is 1205℃, and the heated slab is dephosphorized by high-pressure water; the width is fixed by the fixed width press, and 2 The stand is rough rolling, the rough rolling adopts 3+5 mode, the 7-stand CVC finishing rolling, and the finishing rolling temperature is 892℃; the laminar cooling adopts continuous cooling method 11, and the coiling temperature is 582℃; the reduction rate of the pickling process is set to 60%; the rolling thickness of the galvanizing process is 1.5mm, the annealing furnace heating / averaging temperature is 721℃, the slow cooling temperature is 635℃, the fast cooling temperature is 461℃, the zinc pot temperature is 430℃, the coating thickness is set to 275g / m2, the furnace zone steel strip speed is set to 100m / min, the flattening machine elongation is 1.21%, and the straightening machine elongation is 0.35%.

4. The production method of corrosion-resistant hot-dip galvanized aluminum-magnesium photovoltaic structure steel with a tensile strength of 440 MPa according to claim 1 is characterized in that: Specifically include: The molten iron is pretreated for desulfurization, and the S content of the molten iron leaving the desulfurization station is 0.001%. The heating amount of the desulfurizer in the treatment process is 0.3 tons, the stirring time is 15 minutes, the number of slag removal is greater than 1 time, the slag removal rate is greater than 90%, and the molten iron leaving the station temperature T is 1334℃; the top and bottom combined blowing converter is used for smelting to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process. The weight of scrap steel added to the converter is 51.2 tons, the weight of molten iron added to the converter is 257 tons, the converter tapping temperature is 1638℃, the tapping carbon content is 0.05%, and ferromanganese and ferroaluminum are added to the ladle during the tapping process. Deoxidation and alloying are carried out. Slide plates are used to block slag before and after steelmaking to prevent slag. 1720 kg of high carbon ferromanganese and 1340 kg of ferroaluminum are added during the deoxidation and alloying process. Then the molten steel after converter smelting is subjected to LF refining outside the furnace. The refining temperature is 1542℃. LF refining slag deoxidation and desulfurization are carried out, and the component temperature is adjusted. Alloying treatment is carried out in the early stage of LF treatment. 562 kg of ferromanganese, 420 kg of ferroaluminum, and 220 kg of ferrotitanium are added. 280 meters of calcium wire is fed for calcium treatment. After the alloying is completed, the slag forms white slag and then calcium treatment is carried out. The soft blowing time is 11 min, the soft blowing process prevents the leakage of molten steel, and the LF refining leaving the station temperature is 1581℃; the casting machine pouring overheat is 24℃, the pulling speed is 1.20m / min, and the slag detection is turned on after the ladle pouring, and the gate slide operation is automatically closed to avoid slag in the middle ladle; after the slab quality inspection, it is loaded into the heating furnace, the hot rolled slab thickness is 4.8mm, the heating temperature is 1212℃, the heating time is 172min, the soaking time is 35min, and the furnace temperature is 1195℃. The heated slab is dephosphorized by high-pressure water; the width is fixed by the fixed width press, and the 2 stands for rough rolling, 3+5 mode is adopted for rough rolling, 7 stands for CVC finishing rolling, and the finishing rolling temperature is 880℃; laminar cooling adopts continuous cooling method 11, and the coiling temperature is 570℃; the reduction rate of the pickling process is set to 58%; the rolling thickness of the galvanizing process is 2.0mm, the heating / averaging temperature of the annealing furnace is 708℃, the slow cooling temperature is 629℃, the rapid cooling temperature is 465℃, the zinc pot temperature is 430℃, the coating thickness is set to 275g / m2, the steel strip speed in the furnace area is set to 90m / min, the elongation of the leveler is 1.10%, and the elongation of the straightening machine is 0.30%.

Citation Information

Patent Citations

  • Hot-dip galvanized zinc-aluminum-magnesium alloy coating and preparation method thereof

    CN112680684A

  • Hot-dipped aluminum-zinc or zinc-aluminum-magnesium complex-phase steel with yield strength of 550MPa and manufacturing method thereof

    CN115161542A

  • Low-carbon low-alloy hot-dip aluminum-zinc or zinc-aluminum-magnesium complex-phase steel with yield strength of 450MPa and manufacturing method thereof

    CN115181888A